Elucidating learners’ perceptions and emotions towards interpersonal relations in a foreign language remote teaching - Colombo, Omar (Penerbit Universiti Kebangsaan Malaysia, 2023)
During the COVID-19 pandemic, the second semester 2019/2020 of the French and Italian as Foreign Languages (FFL, IFL) undergraduate programs in a Malaysian University was conducted online as emergency remote teaching (ERT). According to recent studies, ERT affected students learning performance mainly due to loneliness and lack of interpersonal relations (IR). We aimed to improve post-pandemic distance learning and teaching by analysing students’ ERT perceptions and emotions towards IR with peers and lecturers. 78 FFL and IFL students completed two Google Forms surveys on their ERT perceptions and emotions. In each survey, one section focused on IR. The analysis of learners’ scores (based on a five-point Likert scale) utilised Paired Sample t-tests and Pearson correlation test conducted via SPSS. Findings showed ERT contradictory effects. ERT had a negative influence on students’ psycho-emotional status; they were anxious (3.81±0.78) and lacked self-confidence (3.39±0.84) when interacting with peers and lecturers. However, overall, they were satisfied with their IR with lecturers, who were friendly and encouraging during ERT (M=4.05<4.37, SD=0.70<1.06): The higher the value given to IR (with lecturers), the higher the learners’ positive emotions (motivation, enjoyment and self-confidence: r=0.46<0.73, p<0.05) and the final perception and satisfaction of FFL and IFL courses (r=0.35<0.48, p=0.00). Findings have highlighted the significance of the role that lecturers play in students’ Foreign Language progress and positive emotions. Consequently, researchers-lecturers improved the quality of the distance teaching-learning environment, giving more relevance to IR dynamics during synchronous classes, to benefit students’ learning, motivation and enjoyment.